Assessing the Spatial Clustering and Temporal Trends of Dengue Outbreaks in Jhapa District, Nepal - Chapagain, Rajendra Kumar; Upadhyay, Rajeev (The Himalayan Geographers, 2024)
This study investigates the spatio-temporal distribution of dengue fever in Jhapa District, Nepal, an area increasingly affected by vector-borne diseases due to urbanization, climate variability, and environmental conditions. Using Geographic Information System (GIS) tools, secondary health data from 2019 to 2024, and field observations, the study identifies key hotspots of dengue incidence and mosquito breeding sites across 15 local levels. The findings reveal that urban municipalities such as Birtamod and Damak have the highest concentration of confirmed dengue cases, correlating strongly with the presence of outdoor breeding containers like ponds, garages, and pump stations. Statistical analysis shows a significant positive correlation (r = 0.861, p < 0.01) between the number of breeding containers and reported cases. The study concludes that dengue has transitioned from a seasonal to an endemic threat in the district, calling for urgent, targeted vector control strategies, improved environmental management, and sustained community engagement to mitigate future outbreaks.